A conceptual design for my fashion multi sided business model: enhance job Opportunities, upskilling and reskilling B40 community into fashionpreneurs - Ahmad Irfan, Nur A’isyah; Azizi, Nur Aisyah Musyirah; Zulhairy, Sarah Nazurah; Mohammad, Nurulaimi Hannani; Ahmad Dahlan, Abdul Rahman (Kulliyyah of Information and Communication Technology International Islamic University Malaysia, 2022)
The purpose of this conceptual paper is to provide a one-stop clothing center that assembles different types of apparel products or services on a digital platform and in physical stores aligned with the Sustainable Development Goals (SDG) in no poverty, decent work, economic and growth and responsible consumption and production. The global pandemic has made our circumstances challenging, particularly financially. The population most affected is the B40 community, commonly known as the Bottom 40%, whose household income is less than RM4,850. With the Movement Control Order, the majority of the businesses were shut down and this has had an effect on commercial retailers as well. This paper also highlights the pains and challenges faced by the customer segments, the B40 community, unemployed/ retrenched workers, commercial retail customers, donors, and clothing service providers. The Design Thinking (DT) process was applied as the methodology that includes the literature review and the usage of tools like Business Model Canvas (BMC) and Value Proposition Canvas (VPC). This paper also aims to provide customers with trendy and variety choices of clothes and style senses that also promote and encourage people to recycle their unused clothes. In addition, through reskilling and upskilling the B40 community, especially along with the unemployed workers, can gain relevant skills and nurture themselves to be environmental fashionpreneurs.